تأثير المعالجة الحرارية الغازية بغاز الأمونيا على بعض خصائص طبقة الانتشار السطحية في الفولاذ 20 (Latakia University Journal -Basic Sciences Series, 2016)
We have studied in this paper the effect of thermal gaseous using NH3 – gas at some diffusion layers properties of tool steel 20 in temperature range (550 ,650 ,750, 850) 0C , 4h at each one . The purpose of this heat treatment is to get and determine the micro-hardness, fatigue and corrosion resistance. The micro-hardness was determined using Vickers's tester with values ranged between ( 130-435 ) HV. In order to verify these results, we studied the microstructure if the surface layers using metallurgical microscope and SEM (Scanning Electron Microscope). Furthermore the corrosion resistance was studied after immersing it in sea water for two year. قمنا في هذا البحث بدراسة تأثير المعالجة الحرارية الغازية بغاز الأمونيا على بعض خصائص طبقة الانتشار السطحية في الفولاذ 20 عند درجات حرارة ، ولمدة لكل درجة حرارة ، وذلك بهدف زيادة القساوة المجهرية ، والمتانة ، ومقاومة التآكل . تم قياس القساوة المجهرية بطريقةVickers حيث وجدنا أنها تتراوح بين و ، وللتحقق من هذه المعطيات قمنا بدراسة البنية الدقيقة في طبقة الانتشار السطحية باستخدام المجهر التعديني، والماسح الإلكتروني. إضافة إلى ذلك، درسنا مقاومة العينات للتآكل بغمرها في مياه البحر لمدة عامين .